2017
DOI: 10.1631/jzus.b1600454
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis identifies common genes associated with obesity in six obesity-related diseases

Abstract: Obesity has been reported to be associated with many diseases. However, common obesity-induced biological processes have not been evaluated across these diseases. We identified genes associated with obesity and obesity-related diseases, and used them to construct protein‒protein interaction networks. We also analyzed gene ontology (GO) in those genes overlapping between obesity and disease. Our work identifies gene modules common to obesity and obesity-related diseases, which can provide a basis for understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…One of the unexplained issues in the management of obesity is the marked variability in response to the treatment of obesity. Genetic factors play a key role in the individual variability (Su et al, 2017;Bray et al, 2018). The relationship between rs2075654 polymorphism and alleviation of obesity found in the current study suggests that rs2075654 polymorphism could be used to predict prognosis of obesity in children and may contribute to individualized treatment in the future.…”
Section: Discussionmentioning
confidence: 57%
“…One of the unexplained issues in the management of obesity is the marked variability in response to the treatment of obesity. Genetic factors play a key role in the individual variability (Su et al, 2017;Bray et al, 2018). The relationship between rs2075654 polymorphism and alleviation of obesity found in the current study suggests that rs2075654 polymorphism could be used to predict prognosis of obesity in children and may contribute to individualized treatment in the future.…”
Section: Discussionmentioning
confidence: 57%
“…They determine merely 3–5% of the “common”/multifactorial obesity variability, which still remains to be determined [ 50 ]. Highly infrequent single gene mutations (such as LEP , LEPR and POMC ) stand for rare cases of monogenic obesity; however, some of them are also related to polygenic obesity (such as MC4R and FTO ) [ 51 ]. GWAS studies identified multiple common obesity-susceptible loci ( FTO , MC4R , MC3R , SLC6A14 , PCSK1 , TMEM18 , POMC , BDNF and NEGR1) [ 52 ].…”
Section: Genome Wide Association Studies (Gwas) Studies On Psoriasis ...mentioning
confidence: 99%
“…GWAS studies identified multiple common obesity-susceptible loci ( FTO , MC4R , MC3R , SLC6A14 , PCSK1 , TMEM18 , POMC , BDNF and NEGR1) [ 52 ]. They take part in the regulation of body mass system mechanisms, including the neurological trail of appetite and satiety, insulin secretion, adipogenesis, energy and lipid metabolism and gene–environment interactions (diet and physical activity) [ 51 ]. Moreover, recent findings have suggested an overlap of obesity-related single-nucleotide polymorphisms with associated other metabolic diseases (mainly hypertension, type 2 diabetes and cardiovascular disease) [ 51 ].…”
Section: Genome Wide Association Studies (Gwas) Studies On Psoriasis ...mentioning
confidence: 99%
“…They encompass a complex system of body mass regulation: appetite and satiety neurological trail, insulin secretion, adipogenesis, energy and lipid metabolism, gene-environment interactions (dietary and physical activity). Furthermore, recent studies revealed that obesity-related genetic loci overlap with various obesity-related diseases pathways (HT, diabetes, cardiovascular disease) [66]. The FTO gene product is a protein (2-oxoglutarate-dependent nucleic acid demethylase) responsible for DNA repair and energy homeostasis control, which is mainly expressed in hypothalamus nuclei and therefore exerts an influence on fat mass and obesity.…”
Section: Genetic Pathways Of Obesity Abnormal Body Mass Index (Bmi) and Psoriasismentioning
confidence: 99%